Diabetes increases morbidity and mortality rates in peptic ulcer bleeding: An updated systematic review and meta-analysis - Wei, Fengqin; Lin, Xiaoti (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: To elucidate the relationship between diabetes mellitus (DM) and the risk of peptic ulcer complications. Materials and Methods: Fixed effects and random effects models were used for calculating pooled relative risks (RRs) and/or odds ratios (ORs). Subgroup and sensitivity analyses were also performed. Results: Nineteen high-quality investigations were included in the present study. In an analysis of morbidity rates in primary peptic ulcer bleeding (PUB), we calculated a summary OR of 1.433 (95% CI=1.280–1.604) in the random effects model comparing incidence in diabetes patients and in those without diabetes. In addition, a meta-analysis using the fixed effects model indicated a higher 30-day mortality in PUB in DM patients (OR=1.442, 95% CI=1.245–1.671) than in patients without DM. Further subgroup analyses demonstrated that DM patients in prospective cohort studies had an increased risk of 30-day mortality in PUB (RR=1.407, 95% CI=1.177–1.681). A similar result was obtained in a retrospective cohort subgroup, in which DM significantly increased mortality rates in PUB (OR=1.521, 95% CI=1.171–1.976). Conclusion: We provided convincing evidence by a meta-analysis that DM was associated with a 43.3% increase in morbidity rates in PUB and a 44.2% increase in the risk of 30-day mortality in PUB patients.